Exercise hypotension: A retrospective analysis. - Soucie, Luc. (University of Ottawa (Canada), 1994)
This retrospective study assessed the usefulness of a drop and a blunted systolic blood pressure (SBP) response to exercise testing as predictors of multiple or left main coronary artery disease (CAD) as defined by a 'Coronary Score' (CS). Three types of systolic BP response to exercise were used: (1) an increase by more than 20 mmHg (Group I, n = 107), (2) an increase by 20 mmHg or less (Group II, n = 84), and (3) a decrease of at least 10 mmHg (Group III, n = 45). The extent of CAD was significantly greater in groups II and III than in group I (group I, $6.7\pm6.9;$ group II, $9.3\pm7.1;$ group III, $11.7\pm8.5,$ p 0.05). However, the difference was not statistically different between groups II and III which reinforces the value of a blunted SBP response. Treatment outcome also differed between SBP groups. Seventy percent of patients in group I received medical therapy. Over 70% of those in groups II and III underwent coronary angioplasty (PTCA) or coronary bypass surgery (CABG). It was concluded that similarly to a drop in SBP, a blunted SBP response to treadmill exercise testing in patients with known or suspected CAD is a potential indicator of multiple or left main coronary artery disease.
Keywords: Biology, Animal Physiology.